Encrypted Short Message Service Design Using Combination of Modified Advanced Encryption Standard (AES) and Vigenere Cipher Algorithm - Christopher Christopher; Abel Gunawan; Sheila Prima (Engineering, MAthematics and Computer Science (EMACS) Journal, 2022)
Despite the popularity of social media and Internet-based messaging services, Short Message Service (SMS) is still widely used by a lot of people worldwide. However, in this modern era, Short Message Service (SMS) is not a secure way of sending and receive text messages. Anyone with the right privilleges can easily read all the messages sent using SMS service. Therefore, appropriate cryptographic algorithms should be applied to ensure confidentiality of the message content. In this paper, a modified AES with Vigenere Cipher Algorithm will be used to encrypt the text message, hence greatly increasing the security of the sent messages. Avalanche Effect is chosen as a metric for measuring performance of the proposed algorithm and its implementation. The proposed algorithm shows high Avalanche Effect compared to standard AES algorithm.